ESTABLISHING THE PHYLOGENETIC RELATIONSHIP OF THE CAPSICUM GENUS BASED ON THE RPL20 GENE - Loseñara, Jleian Mard M; Ylanan, Lance (Journal of Agriculture and Technology Management, 2020)
Extremely diverse and widespread, the Solanaceae family is of great economic importance, especially one of its genera, Capsicum.  Globally, the production of sweet and chili pepper crops is an important agricultural commodity. Owing to its complex taxonomy, morphological classification, usually based on flowers, is not enough. With the advent of molecular analysis, it is beneficial to create a phylogenetic tree based on genetic data to trace the genus genus' evolutionary relationship, which could serve as baseline work for future studies on the Capsicum genus along with morphological data. In this study, five divergent genes were identified, with rpl20 being the most divergent. A phylogenetic tree generated from Mega X based on the chloroplast plastome rpl20 revealed C. lycianthoides as an outgroup to the other Capsicum species. In addition, C. galapagoense and C. tovarii as more evolutionary diverged species were inferred based on the findings.